Fluorescence spectrum analysis on leaf and fruit using the ImageJ software application - Defrianto Defrianto; Minarni Shiddiq; Usman Malik; Vepy Asyana (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2022)
In this study, ImageJ has been used to process fluorescence spectroscopic images of spinach leaf treated with three variations of sunlight. In addition, apples and tomatoes are also used in imaging by treatment immersed in hot water, pierced, and pressed. Leaf and fruits are illuminated by laser diodes and LEDs of different wavelengths. ImageJ is used to calculate the RGB and gray values of the image with two segmentations, namely the intact image and the threshold. The results show that the thresholding method gives the best results because it automatically reduces the image background. In addition, the threshold background can also be easily set in this imaging. For the spinach leaf experiment, LED with a wavelength of 680 nm showed significant differences in each treatment of sunlight intensity. Meanwhile, in the apple and tomato experiment, the diode laser with a wavelength of 405 nm showed significant results. Both types of fruit with this puncture treatment turned out to provide higher intensity than pressed fruit.